PERANAN PEMERINTAH KOTA TANGERANG DALAM PENANGGULANGAN DAN PENCEGAHAN BANJIR TAHUN 2020 - Chrisdawati Angrelia; Rendy Prihasta; Anjas Chusni Mubarok; Wahyu Kartiko Utami (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
This study examines the role of the Tangerang City Government through the Regional Disaster Management Agency (BPBD) in dealing with floods that occurred in early 2020. The research method used is descriptive qualitative method, with data collection techniques namely observation and interviews. The results of this study indicate that the Tangerang City BPBD implemented a flood prevention and mitigation strategy through activities carried out four times a year. These activities take the form of disaster simulations, seminars, and training on how to deal with floods. Besides that, synergy between the City Government and the community is also needed, because community participation is also needed in suppressing the number of floods in the city of Tangerang.